Imaging the plate boundary between Greenland and North America within the Kane Basin by means of geophysical data - Ehrhardt, Axel; Schnabel, Michael; Damm, Volkmar; Piepjohn, Karsten (Geophysical research letters, 2016)
The Nares Strait is a waterway separating NW Greenland and North America. The nature of the Nares Strait has been subject of discussion for decades, especially if it represents a transform fault that compensated the opening of the Baffin Bay in the Paleogene as Alfred Wegener supposed in 1912. The Kane Basin in the central part of Nares Strait provides an opportunity to cross the proposed fault. Geophysical data were acquired in 2001 and 2010, including among others multichannel and wide‐angle seismic data. The eastern part of the Kane Basin is characterized by a solid platform most likely representing a continuation of the Paleoproterozoic Inglefield‐Mobile‐Belt (Greenland). In the western part, a sedimentary basin with northwestward tilted and eroded layers of Cretaceous age can be resolved. The transition between those two units shows the plate boundary between Greenland and North America and can be considered as a relic of the Wegener Fault. Key Points Seismic and potential geophysical data image the plate boundary between Greenland and Ellesmere Island The Kane Basin can be subdivided into two structural units The transition between both units is interpreted as relic of the Wegener Fault